Role of the nurse in preventing or reducing increase intracranial pressure following craniotomy - Abdelmowla, Rasha; Essa, Abdelhakeem; Abdelmaged, Esmat (International Journal of Advanced Nursing Studies, 2017)
Background: Increase intracranial pressure following craniotomy is common and different measures should be taken to prevent or treat it promptly. Aim: Preventing or reducing increase intracranial pressure following craniotomy. Research design: Quasi-experimental.Subjects and methods: All nurses (26) in neurosurgery department at Assiut Neurological, Psychiatric and Neurosurgery University Hospital, in addition to a sample of 124 patients after craniotomy. Control group (62 adult patients before implementing the nursingÂ Â Â educational program) and study group (62 adult patients after implementing the nursing educational program). Nursesâ€™ knowledge and practice were assessed before and after implementation of the nursing educational program. Tools: Structured questionnaire to assess nurses` demographic data and knowledge about intracranial pressure, observation checklist for nurses` practice, patientsâ€™ assessment sheet, and teaching booklet for nurses about postoperative increase intracranial pressure. Results: Highly significant differences were found as regarding nurses` knowledge and nurses` practice pre and post implementing the nursing educational program. Significant difference was found between study and control groups as regarding increase intracranial pressure following craniotomy.Â Conclusion: Nursing educational program had a significant effect on preventing or reducing postoperative increase intracranial pressure.Recommendation: Nurses should have continuous education through programs, workshops, seminars and/or training courses to maintain high quality care.